O Ensino de Língua Portuguesa na Educação Básica: uma análise enunciativa da escrita no Ensino Fundamental Brasileiro - Martins, Gabriela Schmitt Prym (2021)
This work which theme is the conception of language present in high school textbooks of first language (recommended by the National Plan of the Didactic Book - PNLD) in relation to the concepts delimited by the Theory of Enunciation, according to Émile Benveniste, as reader of Ferdinand de Saussure. To accomplish this, it was necessary to reflect, as a theoretical support, of measures that regularize the brazilian education, Portuguese language teaching and the use of textbooks in the Brazilian public school through documents such as the LDB (1996) and the Guides of the National Plan of the Didactic Book - the PNLD (2012). When analyzing what language perspective is derived from textbook activities, we adopt as theoretical principles, the concepts of language thought by Ferdinand de Saussure, father of modern linguistics in his Course of General Linguistics (2012) and by Émile Benveniste, linguist of the enunciation that took into consideration the saussurian concepts in his Problems of General Linguistics I and II (1989; 2005). As a method of analysis of our work, which is characterized as a bibliographic, descriptive, exploratory and qualitative research, we adopted guiding questions that sought to understand the concept of language in the activities of chapters of didactic books of High School indicated by the PNLD in the last three Guides. When discussing the analyzes, we realized that there is no consistency in the language approach carried out in textbooks, which may cause an inconsistency in the teaching and learning of young people of the Brazilian public school